QCD sum rules calculation of heavy Lambda semileptonic decay - Dosch, H. G.; Ferreira, E.; Nielsen, M.; Rosenfeld, R. (Elsevier B.V., 1998)
We set up sum rules for heavy lambda decays in a full QCD calculation which in the heavy quark mass limit incorporates the symmetries of heavy quark effective theory. For the semileptonic Lambda(c) decay we obtain a reasonable agreement with experiment. For the Lambda(b) semileptonic decay we find at the zero recoil point a violation of the heavy quark symmetry of about 20%. (C) 1998 Published by Elsevier B.V. B.V. All rights reserved.